Ring of fire - Blair, Lawrence; Blair, Lorne (Bantam Books, 1988)
"This is the story of a unique ten-year voyage of exploration amongst the steamy islands of the volcanic Indonesian archipelago. It begins with more bravado than common sense, when we found ourselves on the island of Celebes in the South China Sea..."--Back cover.